Nano-Yarns Reinforced Silk Fibroin Composites Scaffold for Bone Tissue Engineering (Journal of Fiber Bioengineering and Informatics, 2012)
In this paper, novel nano-yarn reinforced scaffolds were fabricated and further biomineralized bysubmerging in 10 × Simulated Body Fluid (SBF). The compressive strength of P(LLA-CL)/Silk Fibroin(SF) nano-yarns reinforced scaffold was 1.72 ± 0.50 MPa and its porosity is 82.8%. Fourier TransformInfrared Spectrum (FTIR) and X-ray Diffraction (XRD) data confirmed the mineral phase was made ofHydroxyapatite (HA). MC3T3-E1 cell proliferation and differentiation on the scaffolds were evaluated.In vitro biological evaluation showed that HA coated scaffolds provided higher cell proliferation efficiency(t-test, P › 0:05) than uncoated scaffolds.